Gut Microbiome Alters the Activity of Liver Cytochromes P450 in Mice With Sex-Dependent Differences - Jourová, Lenka; Vavreckova, Marketa; Zemanova, Nina; Anzenbacher, Pavel; Langova, Katerina; Hermanova, Petra; Hudcovic, Tomas; Anzenbacherova, Eva (Frontiers in Pharmacology, 2020)
Sexual differences and composition/function of gut microbiome are not considered as the most important players on drug metabolism field; however, from the recent data is obvious that they may significantly affect the response of patient to therapy. Here, we evaluated the effect of microbial colonization and sex-differences on mRNA expression and enzymatic activity of hepatic cytochromes P450 (CYPs) in germ-free (GF) mice, lacking the intestinal flora, and control specific pathogen-free (SPF) mice. We have observed the significant increase in the expression of Cyp3a11 in female SPF mice compared to male group. However, the sex-differences were erased in GF mice and the expression of Cyp3a11 was about the same in both sexes. We have also found higher Cyp2c38 gene expression in female mice compared to male mice in both SPF and GF groups. Moreover, these changes were confirmed at the level of enzymatic activity when female mice exhibit higher levels of functional CYP2C than male in both mice groups. Interestingly, we have observed the same trend like with CYP3A enzymes: diminishing the changes between sexes in GF mice. The present data indicates that the mouse gut microbiome play an important role in sustaining the sexual dimorphism in hepatic gene expression and metabolism.